Factors Affecting Purchase Intention of Laptop in Nepal - Rai, Bharat; Rai, Bhula Nath (KMC Research Journal, 2020)
The main objective of the study was to explore the factors affecting purchase intention in the buying of laptops in the Nepalese market. Product quality, product price, and brand image are taken as independent variables to examine the impact on purchase intention. Primary data has been used in the study. Data were collected through a structured questionnaire in the six-point Likert scale from laptop users in the Nepalese market. Convenient sampling was used for the study and Kathmandu was the sampling location. A total of 385 respondents were the sample size of the study. SPSS software has been used to process and analyze the primary data. Mean Standard Deviation, Correlation, and Regression analysis techniques have been used to analyze the collected data.The research found that there is a significant positive relationship of all three independent variables like product quality, product price, and brand image with the dependent variable purchase intention. Moreover, it is found that there is a significant and positive influence of product price and brand image on purchase intention towards the laptop in the Nepalese market. But, it is found that the product quality has no significant influence on the purchase intention towards the laptop in the Nepalese market.